Using “threshold concepts” as a framework for teaching information literacy - Alfredsson, Veronica; Pernler, Tobias (Septentrio Conference Series, 2020)
We would like to explore the idea of threshold concepts as a framework for information literacy (IL) instruction in a higher education setting. Threshold concepts are central to a discipline; difficult to learn, but once understood, impossible to “unlearn”. They are implicitly incorporated in practitioners’ day-to-day work, and form part of the tacit knowledge in a profession. Threshold concepts are thus both taken for granted and difficult to teach; they have become so internalized by the expert that it is easy to forget that they were actually learned at some point. This could lead to a failure in appreciating how hard the concepts can be to master for the novice. According to Hofer, Hanick & Townsend (2018), possible threshold concepts relevant to IL-instruction are: authority; format; information commodities; organizing systems; research process. As we came across these ideas, we asked ourselves how teaching librarians could utilize this approach when helping students cross the IL thresholds. For example, when teaching how to check the authority of a source, how do we help students handle the distinction between trust and truth? When promoting the library as a free resource, how can students understand the information economy? Starting with a brief presentation of the idea of threshold concepts, and an introduction to the IL-specific concepts, we would like to invite the round table participants to reflect upon their own approaches when teaching IL. The discussion will be structured around questions such as: What concepts do you normally find students have difficulties grasping? When did you yourself master those concepts? How did that happen? How can that understanding help you as a teacher to facilitate your students’ learning of the concepts? Possible outcomes of the discussion may entail new didactic ideas, as well as tentative new IL-related threshold concepts.